Evaluation of indoor positioning based on Bluetooth Smart technology - Dahlgren, Erik; Mahmood, Hasan (My University, 2014)
Nowadays, positioning technologies are used in a wide variety of areas such as providing driving directions and tracking valuable goods to name a few. Since the introduction of the global positioning system(GPS), it has become a de facto standard for outdoor positioning applications. In contrast to this, no similar widespread technique is available for indoor positioning or in areas where GPS is unavailable. Extensive research have been devoted to exploring the topic based on a variety of technologies such as Wi-Fi, Bluetooth, Zigbee and ultra wideband radio. None of these have successfully made it into a widely accepted standard, although signi cant progress has been made. In 2010 a completely new Bluetooth technology, referred to as "Bluetooth low energy" or "Bluetooth smart" was released that promises among other things ultra low power consumption, changed radio frequency properties and a completely new software stack. No academic work can be found that explores the usability of this new technology in the context of indoor positioning. This Master thesis is the rst project to evaluate the suitability and the applicability of this new technology in the context of indoor positioning. A selection of algorithms and approaches are explored, tested, evaluated and compared in a testbed scenario designed for this purpose. Furthermore, the results of these tests are analyzed by examining the received signal strength indicator (RSSI) behaviour, which is the parameter used as basis for the positioning approaches. The evaluation shows that Bluetooth smart is a viable alternative for indoor positioning which o ffers widespread availability in society, reasonable accuracy and low cost deployment. The report also provides essential advice on some important pitfalls when using the technology for positioning applications.
Keywords: Data- och informationsvetenskap; Informations- och kommunikationsteknik; Computer and Information Science; Information & Communication Technology